A Glance at Solow’s Growth Theory - Schilir`o, Daniele (Journal of Mathematical Economics and Finance; Vol 3 No 2(5) (2017): JMEF Volume III, Issue 2(5), Winter 2017, 2018)
This article examines  the growth theory of Robert Solow 1  , which has been a point of reference of economic growth since  the 1950s.  First,  the article  analyzes the  path-breaking  model  of  growth contained  in Solow’s  article  “A Contribution  to the Theory  of  Economic Growt”  published  in   The Quarterly Journal of Economics (1956).  Second,  it looks at the contribution  of Solow to growth accounting  and to the new method of studying capital formation  in economic growth through the vintage ap- proach.  Therefore, the work analyzes the article  “Technical Change and the Aggregate Production  Function”  published in The Review of Economics and Statistics (1957). In the latter  publication,  Solow,  through the aggregate  production  function,  tries  to measure  growth and provide  an explanation  of the nature of technical  progress.   The article  also examines  Solow’s 1960 essay “Investment  and Technical Progress”  based on the hypothesis  of embodied  technological  progress  and the vintage approach.